CADRUL LEGAL DE ORGANIZARE ȘI FUNCȚIONARE A AUDITULUI INTERN - Petreanu, Elena (CEP USM, 2017)
În prezenta lucrare sunt abordate aspectele cadrului legal de reglementare a auditului intern cu evedenţierea problemelor existente în organizarea şi funcţionarea acestuia. De asemenea, este elucidată organizarea internaţională a auditului intern şi posibilitatea preluării practicilor avansate pentru funcţionarea auditului intern din Republica Moldova

In this paper the aspects of the legal framework regulating the internal audit are discussed with the identification of the problems in its or ganization and functioning, it is also elucidated the international organization of the internal audit and the possibility of taking over the advanced practices for the functioning of the internal audit of the Republic of Moldova.
LEGAL FRAMEWORK FOR THE ORGANIZATION AND FUNCTIONING OF THE INTERNAL AUDIT
Keywords: audit intern; managementul riscurilor; standarde naționale; Institutul Auditorilor Interni; internal audit; risk management; audit standards; Institute of Internal Auditors